Parameters Optimized with the Pattern Search Algorithm for Fuzzy Control Based Active Power Factor Correction - Colak, Alperen Mustafa (Electric power components and systems, 2024)
In recent times, the demand for reliable and efficient power systems has intensified, necessitating the need for advanced control methodologies. This study introduces an approach to active power factor correction using Fuzzy Control theory. Unlike traditional power factor correction methods which may suffer from imprecision and slow response times, the proposed fuzzy logic controller (FLC) offers a more adaptive and resilient solution by dealing with uncertainties inherent in power systems. The FLC's inherent ability to handle imprecision makes it a suitable choice for active power systems where parameters can be non-linear and constantly changing. Furthermore, this study describes the design and simulation processes of the FLC for active power correction. Under different load and distribution conditions it demonstrates the FLC's efficacy in maintaining power quality by promptly reacting to disturbances, reducing harmonic distortions, and ensuring consistent power factor levels. Comparative analyses with conventional control methods affirm the superiority of the Fuzzy Control-based approach in terms of accuracy, robustness, and response time.